2021
DOI: 10.3389/fpls.2021.684503
|View full text |Cite
|
Sign up to set email alerts
|

Shoot–Root Interplay Mediates Defoliation-Induced Plant Legacy Effect

Abstract: Shoot defoliation by grazers or mowing can affect root traits of grassland species, which may subsequently affect its aboveground traits and ecosystem functioning (e.g., aboveground primary production). However, experimental evidence for such reciprocal feedback between shoots and roots is limited. We grew the perennial grass Leymus chinensis–common across the eastern Eurasian steppe–as model species in a controlled-hydroponics experiment, and then removed half of its shoots, half of its roots, or a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…In our experiment, successive pinching of the lateral shoots directly reduced the remaining aerial biomass (stem and leaves) by 87.7% (Table 2) and indirectly reduced the root biomass by 8.3% (Table 1). Referring to the explanations provided by Li et al (2021), the gross photosynthetic rate was markedly suppressed immediately after pinching the lateral shoots, whereas the respiration rate greatly improved. However, during the recovery process, these physiological trends were reversed, ascribing the regulation of the distribution of new photosynthate carbon in response to plant tissue damage and biomass loss (Schierenbeck et al 1994, Wang et al 2019.…”
Section: Training Methods' Effects On Sap Bleeding Rate (Sbr) and Bio...mentioning
confidence: 84%
See 1 more Smart Citation
“…In our experiment, successive pinching of the lateral shoots directly reduced the remaining aerial biomass (stem and leaves) by 87.7% (Table 2) and indirectly reduced the root biomass by 8.3% (Table 1). Referring to the explanations provided by Li et al (2021), the gross photosynthetic rate was markedly suppressed immediately after pinching the lateral shoots, whereas the respiration rate greatly improved. However, during the recovery process, these physiological trends were reversed, ascribing the regulation of the distribution of new photosynthate carbon in response to plant tissue damage and biomass loss (Schierenbeck et al 1994, Wang et al 2019.…”
Section: Training Methods' Effects On Sap Bleeding Rate (Sbr) and Bio...mentioning
confidence: 84%
“…Therefore, it can be said that in the PT treatment, cucumber plants used carbohydrates to generate new shoots instead of producing new roots. The same explanation was used by Li et al (2021) to justify the reduced root biomass caused indirectly by the defoliation of grasslands (Leymus chinensis). The authors reported that continuous defoliation of L. chinensis directly aff ected the under-compensatory growth of the shoot Saidi et al (2007) reported that after leaf harvesting of cowpea, photosynthates are directed toward new leaf development at the expense of being stored for grain production or being translocated to the root system for root and nodule growth.…”
Section: Training Methods' Effects On Sap Bleeding Rate (Sbr) and Bio...mentioning
confidence: 98%
“…To test whether there was an additive effect of soil legacy of mixture (M), we calculated and compared the predicted and observed values (PV and OV) of biomass from each plant type. The PV and OV values were calculated using the method of Li et al (2021). The PV of biomass was calculated by averaging the corresponding biomass in the soil legacies of grass (G), legume (L), and forb (F).…”
Section: Methodsmentioning
confidence: 99%
“…The seed source was the same as in Phase 1. In the culture room, the seeds were disinfected with 2% sodium hypochlorite (weight-volume ratio) (Li et al, 2021) and sown in pots with conditioned soil. Sterilized seeds were grown in pots with a fixed density of 18 individuals across all treatments, following a hexagonal pattern to ensure balanced competitive interactions.…”
Section: Testing the Soil Legacy Effectsmentioning
confidence: 99%
See 1 more Smart Citation